Evaluation of small millet genotypes against endemic diseases in mid-western Himalayas - J. KUMAR, BIJENDER KUMAR* and (Indian Phytopathology, 2009)
An attempt has been made to identify the suitable small millet genotypes, which can be exploited for developing resistant cultivars against important endemic diseases present in mid-western Himalayas. Results revealed that nine finger millet genotypes viz; VL 234, SANJI 1, PRM 9802, VL 328, VL 333, ED 201- 5A, VR 708, SANJI 1 and VL 324 were completely free from neck and finger blast disease. However, three genotypes of barnyard millet namely; PRB 402, TNAU 92 and VL 216 showed complete resistance against smuts (grain and head smut) and brown spot diseases, while, seven genotypes of foxtail millet viz; GPUS 27, SiA 3039, SiA 3059, SiA 3066, SiA 3088, TNAU 213 and TNAU 235 were found completely free from brown spot. disease.